(untitled) (Research, Society and Development, 2020)
Numerous physiological and biochemical changes occur when plants are subject to water stress. Therefore, the aim of this study was to evaluate grown, antioxidant response, yield and composition of essential oil of basil plants (Ocimum basilicum L.) when subject to water deficit. The experiment was conducted in a greenhouse and supplied with three water regimes: 100-90% (control), 70-60% (moderate stress), 40-30% (severe stress) of the field capacity for 50 days. Plants subjected to severe water stress showed significant reductions in the development of the shoot, as fresh mass and height. The relative water content in leaves decreased with increasing severity of stress. We observed an increase in the activity of antioxidant enzymes superoxide dismutase (SOD), ascorbate peroxidase (APX), and catalase (CAT) in plants subject to water deficit. Plants subject to moderate and severe stress had a higher oil essential yield, besides changing their chemical composition. A total of 54 compounds were identified in the essential oil from the basil leaves. The phenylpropanoids increased with water deficit and may constitute a secondary antioxidant system, which may assist the primary antioxidant defense system, in order to maintain the levels of hydrogen peroxide in the cells at sub-lethal concentrations to basil plants.